2008
DOI: 10.1021/jf8014415
|View full text |Cite
|
Sign up to set email alerts
|

Obtention and Characterization of Phenolic Extracts from Different Cocoa Sources

Abstract: The aim of this study was to evaluate several cocoa sources to obtain a rich phenol extract for use as an ingredient in the food industry. Two types of phenolic extracts, complete and purified, from different cocoa sources (beans, nibs, liquor, and cocoa powder) were investigated. UPLC-MS/MS was used to identify and quantify the phenolic composition of the extracts, and the Folin-Ciocalteu and vanillin assays were used to determine the total phenolic and flavan-3-ol contents, respectively. The DPPH and ORAC as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
70
2
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 19 publications
7
70
2
7
Order By: Relevance
“…32 µg/g ff-dw) and 9.7-10.7 % (9.57 ± 0.09-33.84 ± 0.10 µg/g ff-dw) of the total flavanol content, respectively, whereas quercetin was present in very low quantities in raw cocoa beans representing less than 1.7 % (0.60 ± 0.09-2.79 ± 0.09 µg/g ff-dw) of the total flavanol levels. The presence of these same flavanols has been previously reported in the cocoa beans and different cocoaderived products by Andres-Lacueva et al [5], Ortega et al [8], and Pereira-Caro et al [20]. It was demonstrated that all of the cocoa types had similar qualitative profiles but different amounts of the individual flavanols.…”
Section: Changes In the Profile And The Levels Of Anthocyanins Duringsupporting
confidence: 74%
See 1 more Smart Citation
“…32 µg/g ff-dw) and 9.7-10.7 % (9.57 ± 0.09-33.84 ± 0.10 µg/g ff-dw) of the total flavanol content, respectively, whereas quercetin was present in very low quantities in raw cocoa beans representing less than 1.7 % (0.60 ± 0.09-2.79 ± 0.09 µg/g ff-dw) of the total flavanol levels. The presence of these same flavanols has been previously reported in the cocoa beans and different cocoaderived products by Andres-Lacueva et al [5], Ortega et al [8], and Pereira-Caro et al [20]. It was demonstrated that all of the cocoa types had similar qualitative profiles but different amounts of the individual flavanols.…”
Section: Changes In the Profile And The Levels Of Anthocyanins Duringsupporting
confidence: 74%
“…Among these compounds, monomeric flavan-3-ols (37 %), such as (−)-epicatechin and (+)-catechin, as well as procyanidins (58 %) with various degrees of polymerization are the most important ones [5,6]. The most common procyanidins are mixtures of dimers, trimers, tetramers, oligomers, and polymers with (+)-catechin and (−)-epicatechin as constitutive units linked mainly through 4 → β6 or 4 → β8 bonds [7,8]. Anthocyanins (4 %) are also an important group of flavonoids occurring in raw cocoa beans.…”
Section: Introductionmentioning
confidence: 99%
“…Levels of total phenolic determined by the method of free radical scavenging capacity was determined by DPPH method with slight modifications (Ortega et al, 2008). Folin-Ciocalteu using gallic acid as standard (Lee et al, 2003).…”
Section: Analysis Of Beras Kencur Drinkmentioning
confidence: 99%
“…Estudios previos de varios autores han demostrado que los flavanoles y dímeros ya mencionados son los más abundantes en el cacao y sus derivados. Además, las procianidinas halladas son características del cacao y del chocolate [39]. Estas últimas están constituidas por unidades de flavanoles (epicatequina principalmente) con enlaces 4→6 o 4→8 formando una mezcla de trímeros, tetrámeros y polímeros de hasta 10 unidades [24,25,[39][40].…”
Section: Etapa Final (F6 Y F8)unclassified
“…Además, las procianidinas halladas son características del cacao y del chocolate [39]. Estas últimas están constituidas por unidades de flavanoles (epicatequina principalmente) con enlaces 4→6 o 4→8 formando una mezcla de trímeros, tetrámeros y polímeros de hasta 10 unidades [24,25,[39][40]. Tanto los flavanoles como las procianidinas han sido relacionados con las propiedades antioxidantes atribuidas al cacao.…”
Section: Etapa Final (F6 Y F8)unclassified